THE USE OF TELESSAÚDE TO IMPROVE HEALTH SERVICES - Cristina Condé, Renata; Pereira Martins, Aucirlândia; Gabriel Santos Silva, Diogo; de Oliveira Neto Silva, Suede; Gomes de Araújo Magalhães, Paloma; Gomes Versiani, Lamonielly; Gonçalves Ferreira, Aline; Ferreira Moura Ribeiro, Eduardo; Bianca Leite Batista, Larissa; Verdade Gonçalves Ramos, Lavínia; Carolina Rodrigues dos Santos Schramm, Joana; Carolina Costa Maia Pinheiro, Ana; et al. (Health and Society, 2023)
Objective: to identify the impacts of telessaúde in the health field. Methods: an integrative literature review study was conducted through the databases: Virtual Health Library (VHL), Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library Online (SciELO) and Nursing Database (BDENF). Results: regarding the thematic approach of the articles, the framework of the productions raised in two categories focused on the importance of the use of Information and Communication Technologies (ICT) in auditing and the second addresses the importance of ICT in health in general. Conclusion: in view of the studies analyzed, it is understood that telessaúde, as a strategy, has a significant potential to expand and qualify access to health care, continuing education and the promotion of the quality of life of the population in different locations. The implementation of national policies and specific legislation are important for the progress of telessaúde initiatives in the different scenarios.